FRAKSINASI DAN IDENTIFIKASI SENYAWA ANTIKANKER EKSTRAK KULIT BATANG Rhizopora mucronata SERTA UJI TOKSISITASNYA TERHADAP LARVA UDANG (Artemia salina Leach) - Hartiwi Diastuti; Suwandri Suwandri (Molekul, 2009)
Investigation the anticancer potency of R. mucronata has not been carried yet. This research were aimed to extract the bioactive compound of R. mucronata with various organic solvents, examine their toxicity againts A. salina Leach larv. and identify the toxic compounds from R. mucronata steam bark.The extraction of R. mucronata steam bark were peformed by maseration with n-hexane, chloroform, ethylacetate and methanol, repectively. The extracts were examined their toxicity againsts A. salina Leach larv. The highest activity extracts was fractionated performed by coloumn chromatography. The fractions respectively was examined their toxicity againts A. salina Leach larv. Identification of toxic compound was carry out using gas chromatography-mass spectrometry (GC-MS).The chloroform extracts of R. mucronata had toxic character. Toxicity test to A. salina Leach larv. The Result showed that the chloroform fraction 1 (C1) of R. mucronata steam bark had LC50 equal to 301.50 ppm. Phytochemical study showed that the active fractions contained terpenoid. Bioactive compound from R. mucronatasteam bark were dioctyl phthalate and cyclopropyle azulene decahydro-1,1,7-trimethyl-4-methylene.